Records of Carnidae from the collection of Miroslav Barták (Diptera: Carnidae), with the description of five new species - Stuke, Jens-Hermann; Barták, Miroslav (Zootaxa, 2019)
Carnidae of the genera Meoneura and Hemeromyia in the collection of Miroslav Barták, deposited in the Czech University of Life Sciences (Prague) have been studied. Five species are newly described: Meoneura artoodetoo spec. nov. (Uzbekistan), Meoneura baechli spec. nov. (Italy), Meoneura gnomi spec. nov. (Uzbekistan), Meoneura joedaltoni spec. nov. (Italy), and Meoneura mucki spec. nov. (Uzbekistan). Additional 21 species of Meoneura and 1 species of Hemeromyia are recorded with first records from Algeria, Andorra, Austria, Bulgaria, Czech Republic, France, Italy, Slovakia, Ukraine, and Uzbekistan.